Ni-catalyzed highly enantioselective synthesis of sulfur protected P-stereogenic supramolecular phosphine - Koshti(S), Vijay S.; Chandanshive, Amol C.; Mote, Nilesh R.; Chikkali, Samir H. (Journal of Chemical Sciences, 2021)
As phosphines readily invert, the synthesis of P-chiral phosphines is a challenging task and has been rarely investigated. We report the synthesis of a nickel complex [Ni-((S,S)Me-FerroLANE)(phenyl)(I)] (Ni-Cat.1) and its performance in a P-C coupling reaction to generate P-chiral phosphine. The Ni-Cat.1 was synthesized by mixing ligand (S,S) Me-FerroLANE with the metal precursor [(diphenylphosphanyl)nickel(phenyl)(I)] in good yield. Ni-Cat.1 was characterized using different spectroscopic and analytical techniques. Treatment of racemic methyl(phenyl)phosphine (1) with 1-(3-iodophenyl)urea (2) produced the corresponding P-chiral supramolecular phosphine (3). Optimization of reaction parameters produced sulfur protected phosphine N-(3-(methyl(phenyl)phosphorothioyl)phenyl)formamide (3') with excellent enantiomeric excess (99% ee) and moderate conversion (51%).
Keywords: Asymmetric synthesis; Nickel catalyst; P-C coupling; P-Stereogenic phosphine; supramolecular ligands

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Thermally stable P-chiral supramolecular phosphines, their self-assembly and implication in Rh-catalyzed asymmetric hydrogenation - Chandanshive, Amol C.; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry-A European Journal, 2024)
P-chiral supramolecular phosphine ligands are crucial for asymmetric transformations, but their synthesis is tedious. We report a one-step synthesis of thermally stable P-chiral supramolecular phosphines and their performance in the asymmetric hydrogenation of functionalized alkenes. A rational designing and synthesis of (R, R)-QuinoxP* ligated palladium complex (Pd-2) in excellent yield is reported. This Pd-2 catalyzed a direct P-C coupling of 2,3-dihydro-1-H-phosphindole (A1)/1,2,3,4-tetrahydrophosphindoline (A2) with 1-(3-iodophenyl)urea (B1)/2-iodo /6-hydroxy pyridine (B2) and,produced corresponding ligands L1-L3. The P-C coupling between A1 and B2 produced 6-(2,3-dihydro-1H-phosphindol-1-yl)pyridine-2(1H)-one (L2) with an excellent enantiomeric excess of up to 99 %. L2 was found to be remarkably stable even at 150 degrees C and did not oxidize/hydrolyze for at least 24 hours in open air. Such thermal stability and an impediment to oxidation are unprecedented. L2 self-assembled and produced L2-C1 (Pt), L2-C2(Pd), and L2-C3(Rh) assemblies. The utility of the self-assembled P-chiral ligand was demonstrated in the Rh-catalyzed asymmetric hydrogenation (AH) of functionalized olefins. The L2-C3 catalyzed AH of functionalized alkenes and delivered chiral products with excellent enantioselectivity of >99 %. A small library of 16 substrates was subjected to AH using L2-C3 to produce chiral compounds with excellent conversion and ee.
Keywords: asymmetric hydrogenation; Asymmetric phosphination; P-chiral phosphine; Self-assembly; Supramolecular phosphine

Direct synthesis of phosphine-phosphite ligand and its implication in asymmetric hydrogenation of functionalized olefins - Chandanshive, Amol C.; Khopade, Kishor V.; Chikkali, Samir H. (Chemistryselect, 2026)
Phosphine-phosphite (P-OP) ligands constitute a privileged class of chiral ligands in asymmetric catalysis owing to their modular structures and tunable steric and electronic properties. Herein, we report a direct, one-pot, synthesis of a new flexible P-OP ligand (L) derived from BINOL-PCl and its in situ complexation with rhodium (Rh) for catalytic evaluation. The resulting Rh/L system efficiently hydrogenates a diverse library of 19 functionalized olefins under mild conditions, delivering moderate to excellent enantioselectivities, with ee values reaching up to 99%. Several of the hydrogenated products correspond to valuable chiral building blocks relevant to pharmaceutical synthesis, underscoring the practical utility of flexible P-OP ligand architectures in asymmetric hydrogenation.
Keywords: asymmetric hydrogenation; functionalized alkene; ligand design; metal catalyzed; phosphine-phosphite

P-chiral organophosphorus compounds: synthesis, mechanism, and applications - Chandanshive, Amol C.; Chikkali, Samir H. (Chemistry-an Asian Journal, 2026)
The enantioselective synthesis of P-stereogenic compounds has emerged as a central focus in modern asymmetric catalysis, driven by their pivotal roles as ligands (Ls), organocatalysts, and bioactive molecules. Over the past decade, significant advances have been made in developing catalytic strategies that enable precise control over phosphorus stereochemistry, expanding both the structural diversity and synthetic utility of these scaffolds. This review highlights recent progress in two key areas: direct P-C bond formation and desymmetrization. P-C bond-forming approaches include cross-coupling reactions of secondary phosphines or their oxides with aryl, alkyl, or benzyl halides, as well as hydrophosphination of alkenes and alkynes. Desymmetrization strategies encompass nucleophilic substitution at P(V) centers, cyclization, C-H activation (CHA), phenolic -OH activation, and P-O alkylation/arylation. Mechanistic insights into these transformations have been discussed, along with the derivatization of P-chiral products and their applications in catalysis, L design, and bioactive molecule synthesis. This comprehensive overview shall serve as a valuable resource for researchers working in asymmetric organophosphorus chemistry.
Keywords: desymmetrization; Hydrophosphination; P-C cross coupling; P-chiral phosphines; phosphination